Detection of diverse Wolbachia 16S rRNA sequences at low titers from malaria vectors in Kayin state, Myanmar [version 4; peer review: 2 approved, 1 approved with reservations] - Sunisa Sawasdichai; Victor Chaumeau; Tee Dah; Thithiworada Kulabkeeree; Ladda Kajeechiwa; Monthicha Phanaphadungtham; Muesuwa Trakoolchengkaew; Praphan Kittiphanakun; Yanada Akararungrot; Kyi Oo; Gilles Delmas; Nicholas J. White; et al. (Wellcome Open Research, 2019)
Background : Natural Wolbachia infections in malaria mosquitoes were recently reported in Africa, and negatively correlated with the development of Plasmodium falciparum in the vectors. The occurrence and effects of Wolbachia infections outside Africa have not been described and may have been underestimated. Methods : Mosquitoes were collected by human-landing catch during May and June 2017 in ten villages in Kayin state, Myanmar. Closely related species of malaria vectors were identified with molecular assays. 16S rRNA Wolbachia DNA sequences were detected with quantitative real-time PCR. Results: Low titer of Wolbachia DNA was detected in 13/370 samples in six malaria vector species. Sequences were diverse and different from those described in the African malaria mosquitoes. Conclusion: The detection of Wolbachia DNA in malaria mosquitoes from Kayin state warrants further investigations to understand better the ecology and biology of Anopheles-Wolbachia interactions in Southeast Asia.